2006
DOI: 10.3390/ijerph2006030044
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Copper and Butylic Ester of 2,4-Dichlorophenoxyacetic Acid (Esternon Ultra) on Amphibian Embryos

Abstract: Abstract:Cu 2+ and butylic ester of 2,4-Dichlorophenoxyacetic acid as Esternon Ultra (2,4-D) toxicity on Bufo arenarum embryos were evaluated by means of a short-term chronic toxicity test (AMPHITOX). The NOEC values for Cu and 2,4-D were 0.02 mg/L and 2 mg/L respectively. The toxicity profile curves for Cu and 2,4-D were reported. The interactions of the metal and the herbicide were evaluated by combined treatments with different concentrations of Cu and 2,4-D. Although in all cases, a synergistic effect betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In a previous study in Bufo arenarum embryos continuously exposed to the same 2,4‐D CF from the end of their embryonic development, the Lethal Concentrations (LCs) 50 for 24 and 168 h were 4 and 3 mg L −1 CF respectively. Toxicity Profiles (TOPs), isotoxicity curves based on the LCs, were also reported in that study (Pérez‐Coll and Herkovits,2006). Although those values may already imply a risk for amphibian embryos (EPA,2004), based on previous stage‐dependent susceptibility studies, it has been found that certain stages are highly susceptible to noxious agents (Herkovits et al,1997; Castañaga et al,2009).…”
Section: Introductionsupporting
confidence: 53%
“…In a previous study in Bufo arenarum embryos continuously exposed to the same 2,4‐D CF from the end of their embryonic development, the Lethal Concentrations (LCs) 50 for 24 and 168 h were 4 and 3 mg L −1 CF respectively. Toxicity Profiles (TOPs), isotoxicity curves based on the LCs, were also reported in that study (Pérez‐Coll and Herkovits,2006). Although those values may already imply a risk for amphibian embryos (EPA,2004), based on previous stage‐dependent susceptibility studies, it has been found that certain stages are highly susceptible to noxious agents (Herkovits et al,1997; Castañaga et al,2009).…”
Section: Introductionsupporting
confidence: 53%
“…Similarly, a high concentration of N increased malformations in tadpoles, including swollen sac-like bodies, and in narrow-eyed frog (Nyctibatrachus major), cricket frog (Fejervarya limnocharis), green frogs (Rana clamitans), and bullfrogs (R. catesbeiana) [40][41][42]. Pollutants at low concentrations have mixed and additive toxic effects on the development of amphibian embryos [43][44][45][46][47]. Though heavy metals were not detected in TWE and TWE-mixed water samples in July, an increase in malformation of tadpoles suggests that unidentified pollutants at trace levels may increase the teratogenic activity of TWE in a mixed and additive manner.…”
Section: Effects Of Twe On the Malformation Of B Orientalis Embryosmentioning
confidence: 99%
“…There are many toxicological studies involving amphibians like Rhinella sp and Xenopus sp, because they are more sensitive than other vertebrate species to aquatic contaminants [22][23][24][25][26]. This is the reason they are useful for ecotoxicological studies and widely used to perform toxicity bioassays [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%